Aplikasi Edukasi Pemecahan Masalah pada Vulnerability Server Berbasis Web - Ahmad Syaichul Hadi; Mochamad Alfan Rosid (Maranatha University Press, 2021)
This research is purpose to design a virtual machine to simulate cyber attacks and find out how to design and build a virtual machine with a security gap that has been designed, so that it is used as education for web and server developers. The method used in building this system is the waterfall method which starts from designing a system to make it easier to build a system and then collecting data using observations to students of informatics engineering and computer engineering. The results of this system show that the system is able to run well, the guide for working on questions can be understood by the player, the player can inputs flags without problems, the clues provided are understandable and the educational videos provided are easy to understand. From the explanation aboce, the researchers concluded that this system can provide questions and education well